Real-time monitoring of binding events on a thermostabilized human A2A receptor embedded in a lipid bilayer by surface plasmon resonance - Bocquet, Nicolas; Kohler, Josiane; Hug, Melanie N.; Kusznir, Eric A.; Rufer, Arne C.; Dawson, Roger J.; Hennig, Michael; Ruf, Armin; Huber, Walter; Huber, Sylwia (Biochimica et biophysica acta, 2015)
Membrane proteins (MPs) are prevalent drug discovery targets involved in many cell processes. Despite their high potential as drug targets, the study of MPs has been hindered by limitations in expression, purification and stabilization in order to acquire thermodynamic and kinetic parameters of small molecules binding. These bottlenecks are grounded on the mandatory use of detergents to isolate and extract MPs from the cell plasma membrane and the coexistence of multiple conformations, which reflects biochemical versatility and intrinsic instability of MPs. In this work ,we set out to define a new strategy to enable surface plasmon resonance (SPR) measurements on a thermostabilized and truncated version of the human adenosine (A2A) G-protein-coupled receptor (GPCR) inserted in a lipid bilayer nanodisc in a label- and detergent-free manner by using a combination of affinity tags and GFP-based fluorescence techniques. We were able to detect and characterize small molecules binding kinetics on a GPCR fully embedded in a lipid environment. By providing a comparison between different binding assays in membranes, nanodiscs and detergent micelles, we show that nanodiscs can be used for small molecule binding studies by SPR to enhance the MP stability and to trigger a more native-like behaviour when compared to kinetics on A2A receptors isolated in detergent. This work provides thus a new methodology in drug discovery to characterize the binding kinetics of small molecule ligands for MPs targets in a lipid environment. [Display omitted] •A general and elegant procedure to reconstitute membrane proteins in nanodiscs•Robust and flexible nanodiscs immobilization strategies•Antagonists binding kinetics determination on A2A receptor embedded in a lipid environment•Comparison between two widely used drug discovery methodologies